The resistance to physiological shear stresses of the erythrocytic rosettes formed by cells infected with Plasmodium falciparum - K. T. Chotivanich (2018)
Rosetting forces are believed to be an important contributor to the microcirculatory obstruction that occurs in malaria caused by Plasmodium falciparum. In this study, rosettes of erythrocytes from cultures of this parasite were suspended in different media and exposed to shear stresses corresponding to those encountered on the arterial and venous sides of the human circulation. The rosettes formed by infected erythrocytes in malaria culture medium containing 10% AB serum were disrupted easily (approximately 50% being broken) when exposed to very low shear stresses of <0.5 Pa. However, use of higher concentrations of serum strengthened the rosetting binding forces considerably. Suspension of rosettes in a viscous colloid (e.g. dextran) increased the adherence forces between infected and uninfected red cells. The results indicate that rosettes do resist the physiological shear forces that are encountered in the venular side of the circulation and could thus contribute to microvascular obstruction in falciparum malaria.